Utilização do ultrassom modo-B no estudo do sistema reprodutivo de fêmeas suínas - Passos Pequeno, Andréia (2009)
The introduction of real time ultrasound on swine industry has had a strong impact in the development of the reproductive performance evaluation of swine herds. With this technology, it is possible to diagnose gestation precociously, to determine the embryonic and fetal viability, to establish better programs of artificial insemination for each farm; to decrease the time of replacement females without impairing the reproductive performance and to diagnose pathologies of the urogenital tract, like ovarian cysts or urinary infections. Therefore, the mode-B ultrasound represents an excellent tool to improve the reproductive parameters of the farm.